Job Mobility in Britain: Are the Scots Different? Evidence from the BHPS - Axel Heitmüller (Institute for the Study of Labor (IZA), 2003)
The Scottish extension-sample of the British Household Panel Study (BHPS) is used to shed light on differences in job mobility patterns in England and Scotland for both men and women. Based on probit estimates of the overall mobility rate, a decomposition is applied to distinguish between explained and unexplained differences. Furthermore, exploiting data on the number of job changes, a zero inflated Poisson model is estimated to provide information on possible differences in the expected number of job changes. Overall, there is evidence that suggests significant differences in mobility patterns south and north of the Borders; however, these are confined to men. Yet, whether this suffices to justify a heterogeneous labour market policy for the two countries remains to be seen.
Keywords: C25; J62; J60; 330; job mobility; probit decomposition; zero inflated Poisson model; Arbeitsmobilität; Geschlecht; Schätzung; Schottland; England